Comparisons of metabolic syndrome definitions in four populations of the Asia-Pacific region - Lee, Crystal; Huxley, Rachel; Woodward, M.; Zimmet, P.; Shaw, J.; Cho, N.; Kim, H.; Viali, S.; Tominaga, M.; Vistisen, D.; Borch-Johnsen, K.; Colagiuri, S. (2008)
Background: To compare the prevalence of metabolic syndrome (MetS) by four MetS definitions in four Asia-Pacific populations, and to compare the prevalence of individual metabolic components. Methods: Population-based cross-sectional studies from Australia, Japan, Korea, and Samoa were used to assess the World Health Organization (WHO), European Group for the Study of Insulin Resistance (EGIR), modified National Cholesterol Education Program Adult Treatment Panel III (modATPIII), and International Diabetes Federation (IDF) MetS definitions. Age-adjusted MetS prevalences were compared within and between countries and kappa statistics were used to determine the agreement between IDF and the other three definitions. Results: Japanese people had the lowest prevalence of MetS regardless of definition, and Samoans generally the highest prevalence. Age-adjusted prevalences for the four definitions ranged from 16% to 42% in Australia, 3% to 11% in Japan, 7% to 29% in Korea and 17% to 60% in Samoa. With the exceptions of Korean and Japanese males, the highest prevalence of MetS was obtained with the IDF definition. The best overall agreement with IDF MetS definition was for modATPIII, and the worst for EGIR. There were marked differences in the prevalence of MetS between the sexes, with no systematic pattern, and between the prevalences of individual metabolic components. Conclusions: Differences in the prevalence of MetS and its components, using the various definitions, both within and between populations, indicate that caution is required when comparing studies from different countries. Determining the clinical significance of these differences will require prospective outcome studies. © 2008 Mary Ann Liebert, Inc.